Effect of discrete basalt fiber on operational properties of polytetrafluoroethylene - Yeromenko, O.; Tomina, A.-M.; Rula, I. (Problems of Tribology, 2022)
The article examines the effect of discrete basalt fibers on the tribotechnical characteristics of DF-101 polytetrafluoroethylene according to the “disk-pad” scheme under conditions of friction without lubrication. It was established that the introduction of filler leads to decrease in the intensity of wear and the coefficient of friction of the base polymer 1,7 and 360 times, respectively. The improvement of these properties occurs because “anti-friction layer” that is more stable compared to unfilled polytetrafluoroethylene is formed in the process of friction of basalt plastics. As a result, friction occurs according to the “polymer-polymer” scheme. This is confirmed by a profound change in the morphology of the friction surface. For example, deep ploughing furrows and traces of adhesion with the counterbody are observed for polytetrafluoroethylene, while basalt plastics are more resistant to deformations, which, in turn, leads to a reduction of ploughing furrows. A sharp decrease in wear resistance 1,35-3,3 times is observed for basalt plastics containing 30-40 mass.% of fiber. It is probably a consequence of the growth of defects in the volume of the material due to the uneven location of the fiber in the polymer matrix. The confirmation of the presence of defects in the volume of basalt plastics is confirmed by a comparison of the calculated and experimental (hydrostatic) density. It was found that polytetrafluoroethylene loses 10% of its mass at a temperature of 823K, while the temperature of losing 10% of mass increases by 10 degrees for basalt plastic. It was determined that the effective content of the filler in the polymer matrix is 20 mass.%. The obtained basalt plastic (20 mass.% fiber) is recommended in manufacturing rolling and sliding bearings (as anti-friction protection) for tribological units of modern technology operating under the influence of high temperatures, aggressive environments and friction conditions without lubrication.